Characterization of adult plant leaf rust resistance gene Lr34 in Indian wheat genotypes using an STS marker - Pawar, Sushma Kumari; Kumar, Pardeep; Duhan, Joginder Singh; Saharan, Mahender Singh; Bharadwaj, Subhash Chandra; Tiwari, Ratan; Sharma, Indu (Journal of Cereal Research, 2013)
Genetic resistance is the safest, economical and most effective method of protecting the crop. Durable sources of leaf rust resistance often express a partial, growth stage- specific phenotype referred to as adult plant resistance. One such effective and durable leaf rust adult plant resistance gene deployed world over has been Lr34. Because Lr34 works mostly in adult plants and in combination with other rust resistance genes (such as, Lr34/Yr18, Lr46/Yr29, and Yr30), it is difficult to determine its presence in wheat genotypes. Therefore, there is need to look an alternate method of detecting this resistance gene into the germplasm. Consequently upon availability of a diagnostic marker for Lr34, screening for effective allele of the gene was carried out in Indian wheat genotypes. Among 300 elite wheat lines screened, 60 showed presence of the allele. The resulting genotypes were categorized on the basis of wheat agro climatic zones as well as the centers responsible for developing these genotypes. Amongst the zones, North Western Plains Zone is credited with maximum number of genotypes possessing Lr34 gene (33.3%) followed by North Eastern Plains Zone (28.3%), Peninsular Zone (13.3%) and Northern Hill Zones (11.6%). Remaining areas, which included Central Zone and Southern Hills Zone showed 13.2% genotypes amongst Lr34 positives. Considering center wise wheat breeding, PAU, Ludhiana and IARI, New Delhi contributed 16.6% and 11.6% genotypes possessing Lr34 allele, respectively. Identified genotypes can be utilized for further enhancement of genetic resistance in the respective zones and at the breeding centers to provide much needed durable leaf rust resistance.